Kematangan Emosi dengan Stress Belajar Daring pada Siswa SMA di Sukoharjo - Novendawati Wahyu Sitasari; Wara Rachmawati; Alvia Rizqillah; Yuli Asmi Rozali (Fakultas Psikologi Universitas Wijaya Putra, 2022)
Covid-19 has spread to all countries in the world, including Indonesia. This spread affects all sectors, one of which is education. The impact that occurs in the education sector requires that every learning activity be carried out at home boldly. This change in learning patterns is thought to create stress on students, so good emotions are needed. The purpose of this study was to determine the relationship between emotions and the stress of learning to be brave in high school students in Sukoharjo. The subjects involved in this study were Sukoharjo High School students, totaling 268 students. The measuring instrument used is the maturity scale of Singh's theory (1990) and to measure stress the Depression Anxiety Stress Scales (DASS) is one of the commonly used measuring tools. Results Based on the analysis, the sign value was obtained. = 0.00, which means that there is a significant relationship between emotional maturity and stress (sign < 0.05). In the analysis of the r value, the value of t count > from t table (-0.552 > 0.148) at a significance level of 1%, it can be interpreted that emotional maturity has a strong enough relationship with stress. The relationship between these two variables is negative, that is, increasing the emotional value, the lower the stress value.